Public Debt Burden and Corruption in Developing Countries - Rida Srihadiastuti; Mahjus Ekananda (Forum Kerjasama Pendidikan Tinggi, 2024)
The burden of public debt and the spread of corruption are economic development issues because they can hinder growth in the long term. However, based on theories and empirical reviews, the influence of both on economic growth is still ambiguous and inconclusive, because they can decrease or increase economic growth. This study aims to investigate the dynamic effect of public debt burden and corruption on economic growth in developing countries - where they have difficulty paying debt installments and the prevalence of corruption is higher compared to developed countries. Therefore, in this study the Pooled Mean Group-Autoregressive Distributed Lag (PMG-ARDL) method was used to see: the relationship between economic growth and public debt service and corruption in the long term, short-term adjustments of each variable to long-term balance (cointegration), and to see how fast these variables adjust to the long-term if a shock occurs. We use panel data from 41 developing countries, the observation period is from 2002 to 2021. The results show that the public debt service is detrimental to economic growth in both the short and long term. Corruption harms economic growth in the long term, but can increases it in the short term. Corruption exacerbates the negative impact of public debt service on economic growth in the long term.